A Chemically Stable Hofmann‐Type Metal−Organic Framework with Sandwich‐Like Binding Sites for Benchmark Acetylene Capture. Issue 24 (11th May 2020) - Pei, Jiyan; Shao, Kai; Wang, Jia‐Xin; Wen, Hui‐Min; Yang, Yu; Cui, Yuanjing; Krishna, Rajamani; Li, Bin; Qian, Guodong
Abstract: The realization of porous materials for highly selective separation of acetylene (C2 H2 ) from various other gases (e.g., carbon dioxide and ethylene) by adsorption is of prime importance but challenging in the petrochemical industry. Herein, a chemically stable Hofmann‐type metal−organic framework (MOF), Co(pyz)[Ni(CN)4 ] (termed as ZJU‐74a), that features sandwich‐like binding sites for benchmark C2 H2 capture and separation is reported. Gas sorption isotherms reveal that ZJU‐74a exhibits by far the record C2 H2 capture capacity (49 cm 3 g −1 at 0.01 bar and 296 K) and thus ultrahigh selectivity for C2 H2 /CO2 (36.5), C2 H2 /C2 H4 (24.2), and C2 H2 /CH4 (1312.9) separation at ambient conditions, respectively, of which the C2 H2 /CO2 selectivity is the highest among all the robust MOFs reported so far. Theoretical calculations indicate that the oppositely adjacent nickel(II) centers together with cyanide groups from different layers in ZJU‐74a can construct a sandwich‐type adsorption site to offer dually strong and cooperative interactions for the C2 H2 molecule, thus leading to its ultrahigh C2 H2 capture capacity and selectivities. The exceptional separation performance of ZJU‐74a is confirmed by both simulated and experimental breakthrough curves for 50/50 (v/v) C2 H2 /CO2, 1/99 C2 H2 /C2 H4, and 50/50 C2 H2 /CH4 mixtures under ambient conditions. Abstract : A chemically stable Hofmann‐type metal−organic framework is realized for benchmark acetylene capture capacity and separation, mainly attributed to the unique sandwich‐like binding environments constructed by the oppositely adjacent open metal centers and cyanide groups from the two different [Ni(CN)4 ] 2− building units, thus affording a record‐high acetylene uptake at 0.01 bar and very high selectivities for acetylene‐related separation applications.